2003
DOI: 10.1046/j.1471-4159.2003.01830.x
|View full text |Cite
|
Sign up to set email alerts
|

Mitogen and stress response kinase‐1 (MSK1) mediates excitotoxic induced death of hippocampal neurones

Abstract: Activation of the mitogen-activated protein kinase (MAPK/ ERK) signal transduction pathway may mediate excitotoxic neuronal cell death in vitro and during ischemic brain injury in vivo. However, little is known, of the upstream regulation or downstream consequences of ERK activation under these conditions. Magnesium removal has been described to induce hyperexcitability and degeneration in cultured hippocampal neurones. Here, we show that neurotoxicity evoked by Mg 2+ removal in primary hippocampal neurones st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 38 publications
0
27
0
Order By: Relevance
“…Likewise, PC12 cells were exposed to vehicle or 10 ng/ml NGF for 10 min and then processed for Western blotting with anti-pERK antibody (d), anti-pMSK1 antibody (e) or anti-p90RSK antibody (f). The finding that NMDA receptor activation leads to MSK1 phosphorylation is highly relevant in the context of a recent report demonstrating that increased MSK1 phosphorylation is observed during excitotoxicity in cultured neurons and that the activation of MSK1 may, in fact, contribute to the neurotoxicity observed (Hughes et al, 2003). Neurotoxicity in this model is linked to excessive glutamate receptor activation, including activation of NMDA receptors.…”
Section: Nmda-mediated Erk and Msk1 Activation 1161mentioning
confidence: 76%
“…Likewise, PC12 cells were exposed to vehicle or 10 ng/ml NGF for 10 min and then processed for Western blotting with anti-pERK antibody (d), anti-pMSK1 antibody (e) or anti-p90RSK antibody (f). The finding that NMDA receptor activation leads to MSK1 phosphorylation is highly relevant in the context of a recent report demonstrating that increased MSK1 phosphorylation is observed during excitotoxicity in cultured neurons and that the activation of MSK1 may, in fact, contribute to the neurotoxicity observed (Hughes et al, 2003). Neurotoxicity in this model is linked to excessive glutamate receptor activation, including activation of NMDA receptors.…”
Section: Nmda-mediated Erk and Msk1 Activation 1161mentioning
confidence: 76%
“…MSK1 and MSK2 have previously been shown to be critical for both CREB phosphorylation and the induction of CREB-dependent IE genes downstream of ERK1/ 2 and p38 MAPK activation in neurons, ES cells, fibroblasts and macrophages [8,9,38,39]. Previous studies using small molecule inhibitors have suggested a role for a PKC -Raf -ERK -RSK2 pathway in CREB phosphorylation downstream of TCR activation in T cells [31,33].…”
Section: Discussionmentioning
confidence: 99%
“…In neurons, chronic activation of ERK at the nucleus induced by potassium withdrawal triggers non-classical caspase 3 independent cell death that is characterized by plasma membrane damage and nuclear condensation [119]. Activation of ERK has also been shown to be a key mediator in excitotoxicity [120] and ROS [121,122]. By inhibiting ERK activation, Mfn2 may also inhibit neuronal cell death independent of mitochondrial fusion (Fig.…”
Section: The Role Of Mitochondrial Fusion In Cell Death: Mfn1 and Mfnmentioning
confidence: 99%